Design of 3D printers analysis for construction and architecture (Academic journal Industrial Machine Building Civil Engineering, 2022)
As an advanced method of green construction, concrete 3D printing has the advantages of saving materials, energy and time. However, this technology still cannot meet the practical requirements of large-scale production in the construction industry, and it requires further equipment, materials, and software research. In this paper, the classification of 3D printing in the field of construction, the status of research, and acquaintance with existing equipment for concrete 3D printing are considered
Keywords: additive manufacturing; 3D printing; green construction; robotic printers; and concrete printing